Chest radiograph reading and recording system: evaluation for tuberculosis screening in patients with advanced HIV - Dawson, R; Masuka, P; Edwards, D J; Bateman, E D; Bekker, L-G; Wood, R; Lawn, S D (The international journal of tuberculosis and lung disease, 2010)
An antiretroviral treatment (ART) service in Gugulethu township, Cape Town, South Africa. To assess the inter-observer agreement when using the chest radiographic reading and reporting system (CRRS) to detect radiographic abnormalities in patients with advanced human immunodeficiency virus (HIV) associated immunodeficiency being actively screened for tuberculosis (TB). Second, to assess the associated performance characteristics of radiology as a routine screening test for detection of culture-confirmed pulmonary TB. Radiographs from a study in which patients were actively screened for TB just before starting ART were independently reported by two CRRS-certified readers blinded to clinical status. Good kappa statistic agreements between observers were found when reporting any radiological abnormality consistent with TB among all patients (n = 203, kappa = 0.63, 95%CI 0.52-0.73) and among those with culture-confirmed TB (n = 53, kappa = 0.61, 95%CI 0.40-0.83). However, in comparison with sputum culture, the sensitivity (0.68, 95%CI 0.54-0.79) and specificity (0.53, 95%CI 0.45-0.61) of radiology in this patient group were low. This study provides evidence of the good inter-observer agreement using the CRRS standardised reporting methodology when used among patients with advanced HIV-associated immunodeficiency and a high prevalence of culture-proven pulmonary TB. The utility of radiology as a screening test for TB in this patient group, however, remains limited.